Unprecedented Mediterranean Sea warming in 2024: analysis of the driving mechanisms - Napolitano, Ernesto; Carillo, Adriana; Iacono, Roberto; Struglia, Maria Vittoria; dell’Aquila, Alessandro; Palma, Massimiliano; Marullo, Salvatore; De Sabata, Eleonora; Bordone, Andrea; Borzelli, Gianluca Eusebi (Frontiers in Marine Science, 2025)
The Mediterranean Sea has experienced pronounced warming over the past few decades, but since 2022 this trend has accelerated markedly, culminating in 2024, the hottest and most dynamically energetic year of the last four decades. Record-high sea surface temperatures (SSTs) were observed across both the Western and Eastern subbasins. This study examines the spatio-temporal variability of the 2024 temperature anomaly and its driving mechanisms using satellite observations of SST and sea level, surface fluxes from atmospheric reanalysis, Citizen Science in-situ coastal data, and ocean reanalysis products from the Copernicus Marine Service. Following the strong ocean heat uptake during summer 2023, a prolonged phase of reduced ocean-to-atmosphere heat loss maintained SSTs well above climatology through autumn 2023 and winter–spring 2024. In February 2024, SSTs exceeded 15°C in the Western Mediterranean and nearly 18°C in the Eastern basin. During summer 2024, the Eastern Mediterranean underwent an exceptional marine heatwave, with surface temperatures reaching about 29°C by late August. This anomaly was mainly driven by intense air–sea heat fluxes acting on an unusually shallow mixed layer, which amplified upper-ocean heat storage and persistence. Altimeter and model data reveal that 2024 also marked a sharp increase in mean and eddy kinetic energy (EKE), particularly in the Algerian, Northwestern, and Levantine basins, where the strongest SST anomalies were observed. We found that basin-scale geostrophic kinetic energy has increased markedly from 1993 to 2024, with 2024 standing out as an exceptionally energetic year that deviates from the long-term linear trend. Overall, 2024 represents a year of exceptional oceanic conditions in the Mediterranean, with a strong link between the surface warming and enhanced oceanic kinetic energy.